Surgical treatment of left ventricular tumor. Case report - R. M. Vitovsky; V. V. Isayenko; O. A. Rusnak; I. V. Martyshchenko; B. G. Gulak; O. A. Pishchurin (Ukrainian Journal of Cardiovascular Surgery, 2016)
The article describes the clinical case of removal the tumor (fibroma) of left ventricular, what interest because of complexity diagnostic and choice tactic of further surgical treatment.